Seru dan Sehat dengan Badminton (Mengenalkan Olahraga Favorit di Sekolah Dasar) - Mulyana, Agus; Maghfira, Rhaudya Zihan Esa; Siti, Yoane; Rizkia, Yusril Fitra; Rizky, Achmad; Hanif, Salman Al; Annisa, Rahma (Indo-MathEdu Intellectuals Journal, 2024)
Badminton is a sport that is all over the world, including in Indonesia. This sport is not only fun to play, but also provides many benefits for elementary school students. elementary school students. This study aims to explore the benefits of playing badminton for elementary school students in terms of physical health, social development, and motor skills. social development, and motor skills. The methods used were observation and interviews with students and physical education teachers in several elementary schools in Jakarta. in Jakarta. The results showed that playing badminton on a regular basis can improve students' physical fitness, including muscle strength, agility, and coordination. In addition, students also learn important values such as sportsmanship, teamwork, and discipline. Badminton is also proven to improve gross and fine motor skills, as well as reducing stress and anxiety levels in children. anxiety levels in children. This research concludes that badminton is a sport that is not only fun, but also provides a significant positive impact on students' physical and psychosocial development. on the physical and psychosocial development of primary school students. Therefore, it is recommended that primary schools further promote and integrate badminton in their physical education curriculum to support students' holistic development. support students' holistic development